1995
DOI: 10.2307/3432414
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Lymphocyte Responses in Free-Ranging Bottlenose Dolphins (Tursiops truncatus) Are Associated with Increased Concentrations of PCBs and DDT in Peripheral Blood

Abstract: Since 1987, large-scale mortalities of dolphins have been reported along the Atlantic coast of North America, in the Gulf of Mexico, and in the Mediterranean Sea. Autopsied bottlenose dolphins, Tursiops truncatus, which were collected from the large-scale mortality along the Atlantic coast in 1987 to 1988, exhibited opportunistic infections indicative of immune dysfunction. Further, these animals had high levels of chlorinated hydrocarbons, such as PCBs and DDT, that can suppress immune functions. The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
1
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 30 publications
2
88
1
2
Order By: Relevance
“…Previous investigations of contaminant-induced immune suppression in marine mammals have typically correlated impaired immune responses or less specific biomarkers with tissue levels of polyhalogenated aromatic hydrocarbons (PHAHs) such as the organochlorine pesticides and PCBs (Reijnders, 1994;Lahvis et al, 1995;Simms et al, 2000). While providing circumstantial evidence for immune suppression, causal relationships and mechanisms of action could not be established.…”
Section: Discussionmentioning
confidence: 92%
“…Previous investigations of contaminant-induced immune suppression in marine mammals have typically correlated impaired immune responses or less specific biomarkers with tissue levels of polyhalogenated aromatic hydrocarbons (PHAHs) such as the organochlorine pesticides and PCBs (Reijnders, 1994;Lahvis et al, 1995;Simms et al, 2000). While providing circumstantial evidence for immune suppression, causal relationships and mechanisms of action could not be established.…”
Section: Discussionmentioning
confidence: 92%
“…All contaminant values are given as wet weights unless asterisked. Sources: Peneda et al (1980), Adams & Martin (1986), Geraci (1989), Kirby-Smith & Costlow (1989), Morris et al (1989), Jones & Je¡s (1991), Law et al (1991), Leonzio et al (1992), Kuehl et al (1994), Levitus et al (1994), World Health Organization (1994), Corsolini et al (1995), Kuehl & Haebler (1995), Salata et al (1995), Wood & Van Vleet (1996), Kannan et al (1997), McKenzie et al (1997) each population are a¡ected. Furthermore, because only the dorsal ¢ns of the dolphins were examined, and lesions were observed on other parts of the dolphins when they could be photographed, the total levels of prevalence are likely to be higher still.…”
Section: Discussionmentioning
confidence: 99%
“…Recent mass mortalities have highlighted the potential role of contaminants in disease susceptibility (Hall et al 1992;Aguilar & Borrell 1994) and, in controlled experimental conditions, organochlorines and heavy metals have been demonstrated to adversely a¡ect immune function (Swart et al 1994). However, with few exceptions (Lahvis et al 1995), most studies in the ¢eld have focused on recording tissue contaminant levels, but the actual consequences of these burdens on the health of their host populations remain unclear. Information from captive studies and other wild populations or species may be used to make inferences about the impacts of particular contaminant levels on a speci¢c population.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent laboratory studies showed that HAHs increased susceptibility to bacteria (42,48,61), viruses (26,50,62), and protozoan parasites (26). Several investigators suggested associations between epizootics and elevated organochlorine exposure in beluga whales (Delphinapterus leucas) in the St. Lawrence Estuary (63), California sea lions (Zalophus californianus) on San Miguel Island (64,65), harbor seals (Phoca vitulina) in Europe (66)(67)(68), and bottlenose dolphins (Tursiops truncatus) in the Atlantic Ocean (69). At highly contaminated sites in the Great Lakes, doublecrested cormorants (Phalacrocorax auritus) had increased rates of eye infections associated with Pasteurella multocida (70).…”
Section: Introductionmentioning
confidence: 99%